Business Model Canvas : Fabric Fingers Protection / Nur Najihah Izyan Abdul Rahman - Abdul Rahman, Nur Najihah Izyan (2020)
For produce this product, the key partnerships are the material supplier. To produce Fabric Finger Protection, there is need the material such as Lycra fabric and Kevlar fabric in the high amount. So that, if there have the partnership like material supplier, possibly to get the material in a lower cost. Therefore, the manufacturing of Fabric Fingers Protection is also the important one as the partnerships in a company. The manufacturer will use the raw material that were getting from material suppliers to produce the product in a factory. This is because there is no machine or tools that can use to produce the product ourselves. So that, the manufacturer should be the good partnership in this company. To find the best partnerships for the company, there is need to be careful to not to choose the bad partnerships that will make the company loses and bankrupt.